A escrita como invenção de uma adolescente negra, com deficiência física, no encontro com o feminino: uma construção de caso clínico em psicanálise. - Paz, Quezia Menezes da (2023)
In psychoanalysis, adolescence is a construction, an effect of the entanglements of our time. It implies psychic effort in terms of more effective disconnection from parents, the realization of the weakening of references, the inconsistency of the Other, and the confrontation with impasses regarding the body and the reality of sex. In adolescence, the symbolic references of childhood are no longer enough to fulfill this reality (im)possible to symbolize. In clinical practice and listening in a mental health institution, a teenager's narratives pointed to the embarrassment characteristic of this moment. They were impasses that called for a psychic elaboration and, concomitantly, directed to what was possible to create. It was in light of this that writing emerged as his singular invention. To encompass this dimension, we proposed, as a general objective of this research, to discuss writing as an invention of a black teenager with a physical disability, treated in a mental health institution, in the face of the encounter with the feminine, based on Lacanian psychoanalytic propositions. Specific objectives: investigate the construction of the notion of feminine from the Lacanian psychoanalytic perspective; discuss the errancy of adolescent sexuality based on current resonances, regarding the inconsistency of social ties; analyze how the feminine appears in the clinic with a black teenager with a physical disability about her body; analyze the writing of a teenager as a possible invention in the face of the impossible to say about the feminine. The methodological proposal of this research was the construction of the clinical case in psychoanalysis, carried out based on the clinical records of the psychoanalysis practitioner, based on what was experienced in the transference relationship, which allowed an articulation between theory and clinical practice, aiming to support a dimension of the unique to the case. From the construction of the case, the use of writing is reiterated as an adolescent invention and a possible way out of the conflicts experienced at this moment in life. The aim was to contribute with a reading and practice that is more attentive to the adolescent's impasses, with the feminine and with sexuality, as well as with the singularity of the demands of this black teenager with physical disabilities, thus offering theoretical-clinical support for institutional clinical care for adolescent subjects.